The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1109/access.2022.3143035
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Data Mining Technique for Assessing Satisfaction Level With Online Learning for Higher Education Students During the COVID-19

Abstract: All the educational organizations mainly aim at elevating the academic performance of students for improving the overall quality of education. In this direction, Educational Data Mining (EDM) is a rapidly trending research area that utilizes the essence of Data Mining (DM) concepts to help academic institutions figure out useful information on the Student Satisfaction Level (SSL) with the Online Learning process (OL) during COVID-19 lock-down. Different practices have been tried with EDM to predict students' b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 89 publications
(74 reference statements)
0
30
0
2
Order By: Relevance
“…This finding demonstrates that online learning environments are a viable alternative to traditional classrooms. Nonetheless, this study offers significant insights into the design and implementation of successful online learning environments including several satisfaction criteria, such as instructor support, student autonomy, student participation, and communication (Abdelkader et al, 2022;Zamakhsari & Ridzuan, 2015). More theories are applicable in such a research field, for instance, the technology acceptance model (TAM).…”
Section: Recommendations For Researchersmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding demonstrates that online learning environments are a viable alternative to traditional classrooms. Nonetheless, this study offers significant insights into the design and implementation of successful online learning environments including several satisfaction criteria, such as instructor support, student autonomy, student participation, and communication (Abdelkader et al, 2022;Zamakhsari & Ridzuan, 2015). More theories are applicable in such a research field, for instance, the technology acceptance model (TAM).…”
Section: Recommendations For Researchersmentioning
confidence: 99%
“…Several factors determine the effectiveness of online learning, programs, and classes, for instance, student satisfaction, student autonomy, and students' academic achievements (Abdelkader et al, 2022). Nevertheless, designing and executing effective online environments is a complicated process involving many satisfaction factors, including teacher support, student autonomy, student collaboration, and communication (Zamakhsari & Ridzuan, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And one of the biggest limitations is data samples. Abdelkader et al [9] indicated the best approach as well as the ideal dimensionality of the feature subset. The current study's findings clearly corroborate the well-known link between a small number of characteristics and higher predictive accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, no matter how many years have passed or how many changes are made in the education mode, education and cultural inheritance remains to be the essence and treasure of the Chinese nation. As long as we observe carefully, we will find that the traditional culture is affecting every aspect of our life, especially the Guangfu culture to Cantonese (Tegen et al, 2021 ; Abdelkader et al, 2022 ). These traditional cultures are actually the sources of our cultural identity.…”
Section: Introductionmentioning
confidence: 99%